Wood-Derived Vascular Patches Loaded With Rapamycin Inhibit Neointimal Hyperplasia - Xie, Boao; Zhang, Liwei; Lou, Chunyang; Wei, Shunbo; Li, Jing’an; Bai, Hualong; Dardik, Alan (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Patches are commonly used to close blood vessels after surgery. Most currently used materials are either prosthetics or animal-derived; we recently showed that natural materials, such as a leaf, can be used as a patch, but healing of these natural materials is not optimal; rhodamine and rapamycin have been used to show that coating patches with drugs allows drug delivery to inhibit neointimal hyperplasia that may improve patch healing. Wood is abundant and its stiffness can be reduced with processing; however, whether wood can be used as a vascular patch is not established. We hypothesized that wood can be used as a vascular patch and thus may serve as a novel plant-based biocompatible material. Method: Male Sprague-Dawley rats (aged 6-8 weeks) were used for an inferior vena cava (IVC) patch venoplasty model. After softening, wood patches coated with rhodamine and rapamycin were implanted into the rat subcutaneous tissue, the abdominal cavity or the IVC. Samples were explanted at day 14 for analysis. Result: Wood patches became soft after processing. Patches showed biocompatibility after implantation into subcutaneous tissue or the abdominal cavity. After implantation into the IVC, the patches retained mechanical strength. There was a significantly thinner neointima in wood patches coated with rapamycin compared to control patches (146.7±15.32 μm vs 524.7±26.81 μm; p=0.0001). There were CD34 and nestin-positive cells throughout the patch, and neointimal endothelial cells were Eph-B4 and COUP-TFII-positive. There was a significantly smaller number of PCNA and α-actin dual-positive cells in the neointima (p=0.0003), peri-patch area (p=0.0198) and adventitia (p=0.0004) in wood patches coated with rapamycin compared to control patches. Piezo1 was expressed in the neointima and peri-patch area, and there were decreased CD68 and piezo1 dual-positive cells in wood patches coated with rapamycin compared to control patches. Conclusion: Wood can be used as a novel biomaterial that can be implanted as a vascular patch and also serve as a scaffold for drug delivery. Plant-derived materials may be an alternative to prosthetics or animal-based materials in vascular applications.